Using Performative Art to Communicate Research: Dancing Experiences of Psychosis (LEARNing Landscapes, 2020)
This paper highlights a collaborative effort to bring art and science together. In the field of arts-based research, collaboration between social scientists and artists is critical.1Horsfall and Titchen state that “critical creativity as methodology disrupts traditional edges and enables participation of people in the research who are unlikely to engage in philosophical, theoretical and methodological study, but who can understand its assumptions through embodied experience … [It] opens up endless spaces for genuine democratization of knowledge creation” (156). It was this type of democratized space that we wanted to create. We believed that bringing artists and scientists together would contribute to minimizing boundaries that often exist between these two worlds. We found that our collaboration provided a chance for meaningful dialogue and partnership. Additionally, as Jones states, “reaching across disciplines and finding co-producers for our presentations can go a long way in insuring that, rather than amateur productions, our presentations have polish and the ability to reach our intended audiences in an engaging way” (71).